Regional white matter hyperintensity volume predicts persistent cognitive impairment in acute lacunar infarct patients - Li, Tan; Ye, Mengfan; Yang, Guopeng; Diao, Shanshan; Zhou, Yun; Qin, Yiren; Ding, Dongxue; Zhu, Mo; Fang, Qi (Frontiers in Neurology, 2023)
White matter hyperintensity (WMH) is often described in acute lacunar stroke (ALS) patients, but the special relationship between regional WMH volumes and persistent cognitive impairment remains unclear.We enrolled patients with ALS who were hospitalized at the First Affiliated Hospital of Soochow University between Jan. 2020 and Nov. 2022. All patients were assessed for global cognitive function using Montreal Cognitive Assessment (MoCA) scale at 14±2 days and 6 months after the onset of ALS.The manifestations of chronic cerebral small vessel disease (CSVD) were assessed using MRI scan.The distributions of regional WMH were segmented and their relationships with cognitive impairment were evaluated.A total of 129 patients were enrolled. The baseline frontal WMH volume (OR = 1.18, P = 0.04) was an independent risk factor of long-term cognitive impairment after ALS. Furthermore, the presence of WMH at genu of corpus callosum (GCC) at baseline (OR = 3.1, P = 0.033) was strongly associated with persistent decreased cognition. Multivariable logistic regression analysis showed depression (OR = 6.252, P = 0.029), NIHSS score (OR = 1.24, P = 0.011) and albumin at admission (OR = 0.841, P = 0.032) were also the important determinants of long-term cognitive impairment after ALS.Our study found WMH, especially the frontal WMH volume and the presence of WMH at GCC at baseline, independently contributed to long-term lower cognition in ALS patients. This study provided new evidence of the clinical relevance between regional WMH volume and cognitive impairment in ALS patients.